A Proposed Classification for Intrauterine Device Position [228]. (May 2015) - Tal, Raz M.; Reeves, Matthew F.; Hathaway, Mark Joseph; Canela Oleaga, Juan Manuel; Katz, Bob H.; Tal, Michael G.
Abstract : INTRODUCTION: Intrauterine devices (IUDs) are commonly reported as "embedded" or "low-lying" without a shared understanding among imaging specialist and clinicians. A shared nomenclature would facilitate research into the clinical implications of IUD position. We aim to present a classification for accurately describing IUD position based on IUD location in relation to the cervix and the degree of intramural extension of the IUD arms. METHODS: We performed transvaginal ultrasonography and hysterosalpingography before and after each insertion of 100 copper T-shaped IUDs (T380S). At 3, 6, and 9 months postplacement, we performed transvaginal ultrasonography and, if indicated, hysterosalpingography. We classified IUD location as a 1) above the internal cervical os; 2) inferior tip of the IUD is below the internal cervical os; 3) IUD is visible on speculum examination; and 4) IUD is outside the cervix (complete expulsion). We classified the IUD arms as: (0) no intramural extension; (1) unilateral; or (2) bilateral extension into the myometrium. RESULTS: We inserted 99 IUDs, of which 75 continued to 9 months and above the internal cervical os (1) with 0 complete expulsions (4). Of 24 partially expelled or removed for tolerability, 33% IUDs were above the internal os (1), 40% the bottom was below the internal os (2), and 20% the bottom of the IUD was seen through the cervix (3). Forty-seven percent had unilateral (1) and 40% had bilateral (2) intramural extension. CONCLUSION: We present a new classification for IUD position in the uterus. Excellent correlation between hysterosalpingography and ultrasonography findings was demonstrated enabling classification based on ultrasound imaging alone.